PENGARUH METODE EKSTRAKSI TERHADAP KADAR FLAVONOID EKSTRAK ETANOL DAUN BINAHONG(Anredera Cordifolia (Ten.)) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Yuska Noviyanty; Harlina Harlina; Ayu Yulianti Adha (Oceana Biomedicina Journal, 2022)
ABSTRACT Binahong leaf (Anredera cordifolia (Ten)) is one of the plants that empirically contains many secondary metabolites, one of which is flavonoid compounds. This study aims to examine the effect of ethanol extract of binahong leaves (Anredera cordifolia(Ten.)) using maceration and soxhletation extraction methods and will compare the results of identification and assay of extracts of binahong leaves (Anredera cordifolia(Ten.)) using spectrophotometric methods UV-Vis. The extraction process by maceration and soxhletation was carried out to obtain binahong leaf extract (Anredera cordifolia(Ten.)). Then the identification of flavonoid compounds with the addition of Mg and HCl powder which is positive for flavonoids if the color is yellow-orange. Determination of levels of flavonoid compounds from binahong leaf extract (Anredera cordifolia(Ten)) by spectrophotometric method Uv-Vis.The results showed that the leaf extract of binahong (Anredera cordifolia(Ten)) using maceration and soxhletation methods positively contained flavonoids, seen from the color produced, namely orange. And obtained the average level of flavonoid ethanol extract of the leaves of binahong (Anredera cordifolia(Ten)) maceration method is 2.43%. While the average content of flavonoids in the ethanol extract of the leaves of binahong (Anredera cordifolia(Ten)) using the soxhletation method was 1.76%.